2019
DOI: 10.1038/s41598-019-46603-z
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value of black soldier fly larvae reared on common organic waste streams in Kenya

Abstract: In Africa, livestock production currently accounts for about 30% of the gross value of agricultural production. However, production is struggling to keep up with the demands of expanding human populations, the rise in urbanization and the associated shifts in diet habits. High costs of feed prevent the livestock sector from thriving and to meet the rising demand. Insects have been identified as potential alternatives to the conventionally used protein sources in livestock feed due to their rich nutrients conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
170
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(198 citation statements)
references
References 67 publications
17
170
8
3
Order By: Relevance
“…Ca level, the major mineral of BSFL, is dependent on the substrate and tends to increase in the pre-pupae and pupae stage [30]. The calcium content of BSFL found in the present study was higher (18.5 g/kg DM) than in previous studies using a similar substrate (5.36 g/kg [31]; 1.70 g/kg [22]) but lower than common values observed in BSFL (50-86 g/kg [3]). The bioaccumulation of heavy metals in farmed insects has been highlighted as a potential risk for animal feed [32].…”
Section: Discussioncontrasting
confidence: 74%
“…Ca level, the major mineral of BSFL, is dependent on the substrate and tends to increase in the pre-pupae and pupae stage [30]. The calcium content of BSFL found in the present study was higher (18.5 g/kg DM) than in previous studies using a similar substrate (5.36 g/kg [31]; 1.70 g/kg [22]) but lower than common values observed in BSFL (50-86 g/kg [3]). The bioaccumulation of heavy metals in farmed insects has been highlighted as a potential risk for animal feed [32].…”
Section: Discussioncontrasting
confidence: 74%
“…However, in order to sustainably intensify the production of the Jumbo quail, alternative dietary protein sources with lower environmental costs compared to soybeans are required [5]. Examples of such alternative and sustainable protein sources include insect meals such as black soldier fly (Hermetia illucens) larvae meal [6].…”
Section: Introductionmentioning
confidence: 99%
“…Black soldier fly larvae meal contains about 50% protein of higher biological value compared to that of soybean protein [6,7]. Insect meals have been nutritionally evaluated in chickens to some degree [8] but not in Jumbo quails.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that glycine, proline and glutamate are the first, second, and third most abundant AAs in animal tissues, respectively (Wu 2013), supporting the notion that mammals, birds and other vertebrates have particularly high requirements for these nutrients (Hou and Wu 2018b;Liu et al 2019;Meléndez-Hevia et al 2009;Wu et al 2014). Despite the immunological, nutritional and physiological importance of tryptophan, the content of this AA in feedstuffs was often not analyzed due to technical difficulties (e.g., Bryan 2018;Dozier et al 2003;Jamdar and Harikumar 2008;Ravindran et al 2005;Renna et al 2017;Shumo et al 2019). To our knowledge, this is the first report of all proteinogenic AAs, key nonproteinogenic AAs (taurine, β-alanine, ornithine, and citrulline), agmatine, polyamines, creatine, creatine phosphate, creatinine and glutathione in animal-source feedstuffs for guiding the formation of animal diets.…”
Section: Discussionmentioning
confidence: 56%
“…At present, little is known about the content of creatine, polyamines, and oligopeptides in animal-source feedstuffs, most of which are produced by the rendering and animal protein industries to convert wastes into high-quality protein sources, protect the global environment (Meeker and Hamilton 2006), and reduce carbon emissions from animal production (Wu 2018). In addition, the literature shows large variations of these substances and AAs in feedstuffs among different laboratories (e.g., Bryan 2018;Donadelli et al 2019;Frikha et al 2014;Kerr et al 2017;Kim et al 2000;Norberg et al 2004;Renna et al 2017;Shumo et al 2019). These salient variations in published values might be attributable to the raw materials used (e.g., their sources, freshness and microbial contamination), processing technologies for ingredient production, and errors in AA analyses.…”
Section: Introductionmentioning
confidence: 99%